A Pairwise preferential interaction model for understanding peptide aggregation - Kang, Myungshim; Smith, Paul E. (My University, 2010)
A pairwise preferential interaction model (PPIM), based on Kirkwood-Buff integrals, is developed to quantify and characterize the interactions between some of the functional groups commonly observed in peptides. The existing experimental data are analyzed to determine the preferential interaction parameters for different amino acid and small peptide systems in aqueous solutions. The preferential interactions between the different functional groups present in the peptides are then isolated and quantified by assuming simple pairwise additivity. The PPIM approach provides consistent estimates for the pair interactions between the same functional groups obtained from different solute molecules. Furthermore, these interactions appear to be chemically intuitive. It is argued that this type of approach can provide valuable information concerning specific functional group correlations which could give rise to peptide aggregation.
Keywords: Amino acids; Kirkwood-Buff integrals; Pairwise preferential interaction model; Peptide aggregation; Preferential interactions